Techno-economic comparative analysis of Biomass Integrated Gasification Combined Cycles with and without CO2 capture. (November 2018) - Zang, Guiyan; Jia, Junxi; Tejasvi, Sharma; Ratner, Albert; Silva Lora, Electo
Highlights: Eight BIGCC power systems are compared, which have the LCOE ranges from 13.1 ¢/kWh to 25.9 ¢/kWh. Results indicate the benefits of the Selexol compared with MEA CO2 capture technology. Once the biomass price is lower than 10 /ton, BIGCC power systems without CCS have economic benefits. When the CO2 credit is as high as 90 /ton, the application of CCS technology can reduce the power plant cost. Sensitivity and uncertainty analysis shows the reliability of the analysis carried out in this paper. Abstract: Biomass Integrated Gasification Combined Cycle (BIGCC) power system is a potential application of biomass gasification technology to control CO2 emissions from power generation processes. Nevertheless, there is no study of BIGCC systems that provides detailed techno-economic comparative among its different technological alternatives. This study provides the techno-economic comparative analysis of eight BIGCC system designs that include the technology options of the biomass gasification, the power generation, and the CO2 emission control. Results show that the Levelized Cost of Electricity (LCOE) of these systems is ranged from 13.1 ¢/kWh to 25.9¢/kWh. For current designs, the Selexol CO2 removal technology is more economical than the MEA CO2 capture process. Furthermore, when the biomass price is lower than 10 /ton, the air gasification BIGCC systems can compete with the current electricity generation technology, whereas when the CO2 emission price is higher than 90 /ton, the additional CO2 Capture and Storage technology has the potential to reduce the LCOE of BIGCC systems. Moreover, the sensitivity analysis estimates the impacts of other key economic parameters on the LCOE and Monte Carlo method is used to show the uncertainty of simulation.